A Comparative BAC Map for the Gilthead Sea Bream (Sparus aurata L.). (13th October 2010) - Kuhl, Heiner; Sarropoulou, Elena; Tine, Mbaye; Kotoulas, Georgios; Magoulas, Antonios; Reinhardt, Richard
Abstract : This study presents the first comparative BAC map of the gilthead sea bream ( Sparus aurata ), a highly valuated marine aquaculture fish species in the Mediterranean. High-throughput end sequencing of a BAC library yielded 92, 468 reads (60.6 Mbp). Comparative mapping was achieved by anchoring BAC end sequences to the three-spined stickleback ( Gasterosteus aculeatus ) genome. BACs that were consistently ordered along the stickleback chromosomes accounted for 14, 265 clones. A fraction of 5, 249 BACs constituted a minimal tiling path that covers 73.5% of the stickleback chromosomes and 70.2% of the genes that have been annotated. The N50 size of 1, 485 "BACtigs" consisting of redundant BACs is 337, 253 bp. The largest BACtig covers 2.15 Mbp in the stickleback genome. According to the insert size distribution of mapped BACs the sea bream genome is 1.71-fold larger than the stickleback genome. These results represent a valuable tool to researchers in the field and may support future projects to elucidate the whole sea bream genome.